Seabird-Derived Nutrients Supply Modulates the Trophic Strategies of Mixotrophic Corals - Thibault, Martin; Houlbreque, Fanny; Duprey, Nicolas N.; Choisnard, Noémie; Gillikin, David P.; Meunier, Valentine; Benzoni, Francesca; Ravache, Andréas; Lorrain, Anne (Frontiers in Marine Science, 2022)
The ability of corals to modulate their nutrition strategy in response to variable nutrient supply remains poorly understood, limiting our understanding of energy flow in coral reef ecosystems and thus our comprehension of their resilience to global changes. We used a naturally-occurring nutrient gradient along the reef flat of two seabird-inhabited islets in the SW Pacific to characterize spatiotemporal fluctuations in coastal nutrient availability, and how it modulates the trophic response of the mixotrophic coral Pocillopora damicornis. The clear gradients in dissolved [NOx] and δ15N values of macroalgae and both P. damicornis tissues and symbionts observed along the reef flat during the dry and the rainy season revealed that seabird-derived-N is supplied year-round to the reef flat. Yet, nitrogen isotope values of macroalgae show that the seabirds’ effect on coral reefs varies with sites and seasons. Metrics derived from the SIBER framework revealed that coral nutrition seasonally favoured autotrophy when exposed to higher seabird guano concentrations and at inshore stations, while heterotrophy dominated in corals less exposed to seabird-derived nutrient supply. P. Damicornis is therefore able to cope with large changes in nitrogen supply induced by seabird island communities by switching between autotrophy and heterotrophy. These results shed light on the flexibility of resource sharing within the coral-algae symbiosis and highlight the importance of seabird populations to the functioning of coral reef ecosystems.